Management of Fruit Flies Using Environmentally Safer Pesticide (Spinosad) in Shendi, Sudan - A. Elsanosy Hythum; M. KhairAbbas Amani; M. A. Magid Faiza; H. M. Adam Abubaker (Journal of Agronomy Research, 2020)
The fruit flies of familyTephritidae are considered as serious pests of Mango in Sudan. They cause substantial damage to Mango in all Mango production areas. The application of various pesticides appeared to be ineffective. Therefore, this study was carried out to investigate the efficacy of Spinosad as new promising control measure to the fruit flies. This study was carried out at Shendi area, River Nile State during the period from April 2012 to August 2014, where Pheromone and food bait traps were used for detection and monitoring the fruit flies species in the study area. Spinosad (0.24gŁ) was applied as a partial spraying pesticide. Results indicated that; the application of Spinosad highly decreased the fruit flies numbers. The average number of fruit flies collected in April was (947.22 and 1001.67) for the treated and untreated orchards respectively. The numbers of fruit flies in the treated orchards had decreased gradually during May, June, July and August, 904.7, 760.22, 609.6 and 452.7, respectively, but in untreated orchards for the same months had increased to 1003.67, 1103.67, 1336.67and 1468.67 respectively. However, the infestation level in mango fruits in the treated orchards was found to be 2% compared with 64% for untreated one.
Keywords: Orchards